THE CORRELATION BETWEEN MOTIVATION AND LISTENING PROFICIENCY OF THE SECOND-YEAR STUDENTS OF ENGLISH STUDY PROGRAM OF FKIP UNIVERSITAS RIAU - Putri, Syadza Adila; Hadriana, Hadriana; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out the correlation between motivation and listening proficiency of the second-year students of English Study Program of FKIP Universitas Riau. The sample of this research is one class consisted of 38 students. The class was chosen by using Cluster Random Sampling Technique. There were two data collected in this research which were the data of motivation and listening proficiency. The motivation data was gained by using Attitude/Motivation Test Battery (ATMB) questionnaire by Gardner and the listening proficiency data was gained by holding Test of English as Foreign Language (TOEFL) Preparation – Listening Section. The results show that the motivation of the population is categorized in “good” level and the listening proficiency of the population is “poor” level. Another result shows that there is a correlation between students’ motivation and their listening proficiency to the tune of 31%. In other words, the students’ motivation affects their listening proficiency.Key Words: Correlation, Motivation, Listening Proficiency